Streptomyces zingiberis sp. nov., an endophytic actinobacterium isolated from the root tissue of Zingiber montanum - Rawirat Pansomsuay; Thitikorn Duangupama; Pattama Pittayakhajonwut; Chakapong Intaraudom; Chanwit Suriyachadkun; Ya‐Wen He; Somboon Tanasupawat; Chitti Thawai (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2023)
sp. nov.
Keywords: Genomics and Phylogenetic Studies; Microbial Natural Products and Biosynthesis; Mycobacterium research and diagnosis